Solid shrimp waste derived nanoporous carbon as an alternative bio-sorbent for oxytetracycline removal from aquaculture wastewater - Napat Kaewtrakulchai; Nippit Samattakarn; Sirayu Chanpee; Pornsawan Assawasaengrat; Kanit Manatura; Sutthipoj Wongrerkdee; Apiluck Eiad-Ua (My University, 2024)
Recently, it has been critical to effectively remove oxytetracycline (OTC) from aquaculture wastewater before releasing into the environment. The adsorption process is recognized as an efficient pathway for removing OTC since it is a simple, stable, and cost-effective method. This study aims to develop nanoporous carbon entirely from shrimp waste (SW) via hydrothermal carbonization assisted with KOH activation. Existing KOH significantly increases the porosity of SW nanoporous carbon. The optimal SW porous carbon was obtained using 5 wt.% KOH for activation, which had the largest surface area of 679.51 m2/g with the total pore volume of 0.458 cm3/g. Moreover, the SW porous carbon with the highest porosity was selected for the OTC adsorption. The Langmuir isotherm model and the pseudo-second-order kinetic model match the experimental data, implying that the adsorption mechanism is mono-layered adsorption due to micropores by chemisorption interaction. The adsorption capacity significantly improved by increasing the dosage of SW nanoporous carbon. The SW nanoporous carbon adsorption for OTC is primarily regulated by pore filling affected by hydrogen bonding, and π-π* interaction also plays a significant role. The SW nanoporous carbon showed an efficient OTC adsorption after 5 regeneration cycles. This work demonstrates biomass waste recycling and emphasizes the potential of aquatic food processing waste-derived nanoporous carbon for antibiotic adsorption.
Keywords: Nanoporous; Specific surface area; Carbon fibers; Nanomaterials for catalytic reactions